The Impact of Structural Determinants on Pregnancy Intention and Reproductive Decision Making Among African American Women - (:unkn) unknown (My University, 2021)
ABSTRACTTHE IMPACT OF STRUCTURAL DETERMINANTS ON PREGNANCY INTENTION AND REPRODUCTIVE DECISION MAKING AMONG AFRICAN AMERICAN WOMEN BACKGROUND: Nearly half of U.S. pregnancies are unintended with African American women having the highest rates of unintended pregnancies and many of the poorest pregnancy-related health outcomes. Intersectional approaches are needed to better understand how intersecting oppressions effect pregnancy intentions in African American women’s lives. This study examined African American women’s intersectional identities related to pregnancy intention, experiences accessing reproductive care, and making reproductive decisions. METHODS: This mixed-methods participatory study used Group Concept Mapping (GCM) along with four questionnaires (reproductive history, Adverse Childhood Experiences, Everyday Discrimination Scale, Perceived Stress Scale, and the Patient Health Questionnaire-2 item depression screen). African American women between 18-44 years were recruited and grouped into lower (n=12) and higher (n=12) income groups. Using GCM methods and software, each group engaged in the participatory data collection analysis process across three sessions. Session one included participants brainstorming factors they considered when deciding to become pregnant or not. In session two, after the group brainstorming session, participants were individually tasked with sorting statements into categories and rating from lowest to highest the importance of factors in deciding to get pregnant, preventing pregnancy and using contraceptives. The GCM software generated 102 statements, organized into 8 clusters. Multidimensional scaling analysis created maps later interpreted by participants in session 3. The researcher utilized the maps to generate go-zones and pattern matches to compare responses between groups and were stratified by stress level, trauma history, depression symptoms, and contraceptive use. RESULTS: Three themes emerged from the Group Concept Mapping process: Inward Reflection (autonomy), Relational Reflection (sexual partners), and Outward Reflection (judged by others), which each influenced participant’s pregnancy intention and reproductive decision-making. Everyday discrimination was common. The higher income group more frequently experienced race-based and gender-based discrimination, while the lower-income group more frequently experienced class-based discrimination. CONCLUSION: Interventions to support pregnancy intention and reproductive decision-making need to account for the intersecting oppressive identities within their design. Public health interventions are needed to address the roots of oppression in women’s reproductive lives and have a nuanced appreciation for historical and ongoing policies that can address structural determinants of health.
Keywords: African American Women; Group Concept Mapping; Pregnancy Intention; Racism; Relationship with Medical Providers; Reproductive Decision Making